'Poor, pale, Rusalka' : the polymorphic nature of the heroine of Dvořák's Rusalka : a thesis submitted to Massey University and Victoria University of Wellington in fulfilment of the requirements for the degree of Master of Music in Musicology - Brackovic, Jasna (Massey University, 2014)
Rusalka, the protagonist of Antonín Dvořák’s eponymous opera, is probably one of the most unique operatic heroines. Rusalka’s burning desire to become human in order to be with one and have a soul takes her on an interesting, yet tragic journey. From water nymph to human to will-o-the-wisp, Rusalka goes through three different states and two metamorphoses that leave her desire unfulfilled and cause her to suffer continuously. The two metamorphoses cause Rusalka to remain between the natural and human worlds, both of which reject her. This in turn leads to her eternal suffering. Her tragic fate and constant agony portray her as a victim. And yet Rusalka is also a powerful character who is in command of her own story: as the opera’s sole protagonist, we are encouraged to identify with her perspective. She is constantly present throughout the opera. Even in the scenes that do not require her presence, she communicates with us through absence and through other characters that are, like us, influenced by her presence. And when Rusalka is silent, she connects with us through the language of orchestral music; her mute exterior on stage eludes us and seeks our understanding and sympathy. Thus, her powerful presence and the complexity of her nature draw us as the readers/listeners/spectators to experience Rusalka’s story through her subjective perspective. In order to reveal the nature of the character and how it affects us as readers/listeners/spectators, I will use various approaches, with an emphasis on psychological concepts that will provide a new insight into Rusalka and the opera as a whole. My research will also suggest the impact of fin-desiècle misogyny on Rusalka and specifically her silence, which is the perhaps the most intriguing aspect of the opera and its protagonist. The thesis will follow Rusalka’s journey, from the time and culture of its creation to modern times, as portrayed in some of the more recent dramatic productions that resituate these themes in light of more current perspectives. I will expose in turn the layers in Rusalka: from the libretto and the music, to the use of voice, and finally the playing with meaning in a few representative stage productions. In the second and third chapters, focusing on the libretto and music respectively, I discuss the ways Rusalka articulates her nature, using the Freudian structural model of the psyche for the analysis of the narrative and repetition in the libretto and music. The analysis of music also points toward repetition as a key method, and I suggest connections with the psychological concept of repetition, linked with desire and the death drive, as observed by Slavoj Žižek and Renata Salecl. In the fourth chapter, I focus on the voice, more specifically the cry, in order to explore the ways in which we experience the voice, which I believe is the central element that causes a painful enjoyment (jouissance) in some of us, and in turn is key to our sympathetic empathy with Rusalka. Finally, with Rusalka on stage, I explore the ways in which we, as audience, relate to Rusalka’s suffering, focusing mainly on her silent state. With the addition of the layer of the gaze, I focus on the spectators’ reaction to mute Rusalka and how, in a way, they participate in these moments of suffering precisely through the gaze. Throughout the thesis, I demonstrate how Rusalka communicates with us through the opera’s layers and how in return we respond to them, either by sympathising or identifying with the protagonist.
Keywords: Rusalka; Dvorak; Antonin Dvorak; Opera